Year round performance and cost analysis of a finned single basin solar still. (5th January 2017) - El-Sebaii, A.A.; El-Naggar, M.
Highlights: The performance of a FBLS was investigated experimentally and theoretically. The year round performance of the still was performed. The price of 1 L of fresh water equals 0.28 and 0.31 LE for the still with and without copper fins. The results were inferred that the fin material did not affect still productivity. Abstract: The thermal performance of a finned single basin solar still was investigated experimentally and theoretically using finned basin liner made of different materials such as aluminum, iron, copper, glass, stainless steel, mica and brass. The theoretical model was validate experimentally with a finned basin liner made of copper as example. The year round performance of the still in terms of the monthly average of daily productivity and efficiency was performed. Furthermore, the year round productivity was employed to calculate the cost of one liter of the produced fresh water. The results were indicated that the price of 1 (L) of fresh water equals 0.28 and 0.31 (LE) for the still with and without copper fins. It was also inferred that the fin material did not affect the still productivity. For finned basin liner made of glass and mica, it was found that the price of 1 (L) of fresh water was found to be 0.21 and 0.20 (LE), respectively. Therefore, it is advisable to construct basin liner of finned solar still form mica or glass where they do not corrode in contact with saline water.